Evaluation and management of traumatic diaphragmatic injuries: A Practice Management Guideline from the Eastern Association for the Surgery of Trauma. Issue 1 (July 2018) - McDonald, Amy A.; Robinson, Bryce R.H.; Alarcon, Louis; Bosarge, Patrick L.; Dorion, Heath; Haut, Elliott R.; Juern, Jeremy; Madbak, Firas; Reddy, Srinivas; Weiss, Patricia; Como, John J.
Abstract : BACKGROUND: Traumatic diaphragm injuries (TDI) pose both diagnostic and therapeutic challenges in both the acute and chronic phases. There are no published practice management guidelines to date for TDI. We aim to formulate a practice management guideline for TDI using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. METHODS: The working group formulated five Patient, Intervention, Comparator, Outcome questions regarding the following topics: (1) diagnostic approach (laparoscopy vs. computed tomography); (2) nonoperative management of penetrating right-sided injuries; (3) surgical approach (abdominal or thoracic) for acute TDI, including (4) the use of laparoscopy; and (5) surgical approach (abdominal or thoracic) for delayed TDI. A systematic review was undertaken and last updated December 2016. RevMan 5 (Cochran Collaboration) and GRADEpro (Grade Working Group) software were used. Recommendations were voted on by working group members. Consensus was obtained for each recommendation. RESULTS: A total of 56 articles were used to formulate the recommendations. Most studies were retrospective case series with variable reporting of outcomes measures and outcomes frequently not stratified to intervention or comparator. The overall quality of the evidence was very low for all Patient, Intervention, Comparator, Outcomes. Therefore, only conditional recommendations could be made. CONCLUSION: Recommendations were made in favor of laparoscopy over computed tomography for diagnosis, nonoperative versus operative approach for right-sided penetrating injuries, abdominal versus thoracic approach for acute TDI, and laparoscopy (with the appropriate skill set and resources) versus open approach for isolated TDI. No recommendation could be made for the preferred operative approach for delayed TDI. Very low-quality evidence precluded any strong recommendations. Further study of the diagnostic and therapeutic approaches to TDI is warranted. LEVEL OF EVIDENCE: Guideline; Systematic review, level IV. Abstract : Supplemental digital content is available in the text.